Role of Two Types of Syntactic Embedding in Belief Attribution in Adults with or without Asperger Syndrome - Burnel, Morgane Clémentine; Perrone-Bertolotti, Marcela; Durrleman, Stephanie; Reboul, Anne C.; Baciu, Monica (Frontiers in Psychology, 2017)
The role of syntax in belief attribution is not completely understood in healthy adults and understudied in adults with autism spectrum disorder. Embedded syntax could be useful either for the development of Theory of Mind (ToM) (Emergence account) or more generally over the lifespan (Reasoning account). Two hypotheses have been explored, one suggesting that embedding itself (Relatives and Complement sentences, Metarepresentation account) is important for ToM and another one considering that the embedding of a false proposition into a true one (Complement sentences, Misrepresentation account) is important. The goals of this study were to evaluate (1) the role of syntax in ToM (Emergence vs. Reasoning account), (2) the type of syntax implied in ToM (Metarepresentation vs. Misrepresentation account), and (3) the verbally-mediated strategies which compensate for ToM deficits in adults with Asperger Syndrome (AS). Fifty NeuroTypical (NT) adults and 22 adults with AS were involved in a forced-choice task including +/- ToM tasks (belief attribution, BA and a control task, Physical Causation, PC) under four Interference conditions (silence, syllable repetition, relative sentences repetition and complement sentences repetition). The non-significant +/- ToM x Interference interaction effect in the NT group did not support the Reasoning account and thus suggests that syntax is useful only for ToM development (i.e., Emergence account). Results also indicated that repeating complement clauses put NT participants in a dual task whereas repeating relative clauses did not, suggesting that repeating relatives is easier for NT than repeating complements. This could be an argument in favor of the Misrepresentation account. However this result should be interpreted with caution because our results did not support the Reasoning account. Moreover, AS participants (but not NT participants) were more disrupted by +/- ToM tasks when asked to repeat complement sentences compared to relative clause sentences. This result is in favor of the Misrepresentation account and indirectly suggests verbally-mediated strategies for ToM in AS. To summarize, our results are in favor of the Emergence account in NT and of Reasoning and Misrepresentation accounts in adults with AS. Overall, this suggests that adults with AS use complement syntax to compensate for ToM deficits.